Total Quality Manajemen untuk Meningkatkan Kualitas Output melalui Sistem Kontrol Mutu Madrasah - Ramlah; Ahmad Rifdur Rohman (Nusantara Journal of Islamic Studies, 2023)
The good quality education was not only determined by the teacher, but also influenced by the entire personnel and educational elements, such as; students, administration management, curriculum, vision, mission. Therefore, the total quality manejement not only was positioned as a strategy and apporoach in advencing of educational quality, but also positioned as an integral system of quality improfment in education and the way of life in achieving the objectives effectively and effeciently. Implementation of total quality manajemen in educational institutions boarding school should be implemnetedas an effeort to increase the quality of education that had high competitive power. This strategy should be done continuously in order to optimizly the quality and productivity of education with held on the principle of continous improvement.